Association between serum gamma-glutamyltransferase and stroke in adults from national health and nutrition examination survey (2005–2016): a cross-sectional study - Weiren Yan; Lijia Xu; Ke Xu; Xianglin Liu; Xinsheng Li; Haichen Lv (BMC Cardiovascular Disorders)
Abstract Background Serum gamma-glutamyltransferase (GGT) is an enzyme primarily produced by liver metabolism and serves as an important marker for liver function and alcohol use. However, its relationship with stroke remains largely unclear. Consequently, the present work investigated the link of GGT with stroke in adults. Methods Data of the National Health and Nutrition Examination Survey 2005–2016 were obtained into this cross-sectional study for examining the relation of GGT with stroke. Participants were split into quartiles based on serum gamma-glutamyltransferase (GGT) levels: quartiles 1, 2, 3, and 4 (4–14, 14–20, 20–30, and > 30 U/L separately). Multivariable logistic analysis was conducted in the analysis, along with a p-value for trend. Meanwhile, a restricted cubic spline function was adopted to evaluate the dose-response relationship. Results This study included 30,380 participants, and multivariate regression suggested a positive relationship between serum GGT levels and the risk of stroke. The adjusted odds ratios (ORs) of stroke for the highest versus lowest quartiles of GGT was 1.32 (95%CI, 1.06, 1.64), while the p-value of trend through quartiles was 0.024. Restricted cubic spline analysis revealed a nonlinear, nearly inverted L-shaped relationship of GGT with stroke (p-value for non-linearity < 0 0.001). In addition, a nonlinear positive relation of GGT with stroke was also discovered among women, aged < 60 years, alcohol-drinking, non-smoking, and non-diabetes populations. Conclusion Serum GGT showed a positive and non-linear relation with stroke risk among adults. This relation differed among diverse populations.